Determining Recruitment Quality Through Employer Brand Strength: Analysis of Gamification in Recruitment, Social Media Recruitment, and Digital Leadership - Ni Nyoman Sawitri Sawitri (Dinasti Publisher, 2025)
This study aims to analyze the effect of Gamification in Recruitment, Social Media Recruitment, and Digital Leadership on Recruitment Quality through Employer Brand Strength in MSMEs. Using a systematic literature review approach, this study synthesizes findings from various relevant internationally indexed academic articles. The research method used is a systematic literature review with a descriptive-qualitative approach. Data were collected from reputable international indexed articles obtained through databases such as Scopus, Web of Science, Emerald, Springer, and Google Scholar. The selected literature was analyzed using reduction techniques, data presentation in matrix form, and comparative synthesis to find patterns, similarities, and differences between studies. The results of the study indicate that Gamification in Recruitment, Social Media Recruitment, and Digital Leadership affect Recruitment Quality either directly or indirectly through Employer Brand Strength. The contribution of this study provides guidance for MSME players in designing recruitment strategies that are more attractive, interactive, and candidate experience-oriented so as to increase competitiveness in attracting superior talent in the digital era. The novelty of this research presents a conceptual innovation that combines the dimensions of candidate behavior, organizational strategy, and digital leadership into a single strategic framework to build superior and adaptive recruitment in the era of digital transformation.